785. Association between Prevalence of Laboratory-Identified Clostridioides difficile Infections (CDIs) and CDI Antibiotic Treatment in U.S. Acute Care Hospitals, 2018. (31st December 2020) - Xu, Kerui; Benin, Andrea L; Wu, Hsiu; Edwards, Jonathan R; Li, Qunna; O'Leary, Erin; Leaptrot, Denise; Nkwata, Allan
Abstract: Background: Clostridioides difficile infections (CDIs) are an urgent public health threat, accounting for 223, 900 infections and 12, 800 deaths in hospitalized patients annually. In early 2018, the Infectious Disease Society of America (IDSA) recommended oral vancomycin or fidaxomicin as the first-line antibiotics for CDIs. To track the uptake of IDSA's recommendations, we evaluated the association between CDI prevalence and use of first-line antibiotics in hospitals reporting to the Centers for Disease Control and Prevention's (CDC's) National Healthcare Safety Network (NHSN). Methods: We matched 2018 hospital-level, NHSN data on laboratory-identified CDIs with NHSN antimicrobial use (AU) data for the same time period. Hospitals that submitted < 6 months of either data type in 2018 were excluded. The association between quarterly hospital-level CDI prevalence rates per 100 patient-admissions and use of CDI antibiotics (oral vancomycin plus fidaxomicin) per 1, 000 days-present was evaluated using Pearson's linear correlation coefficient and using Goodman and Kruskal's gamma (G) on ordinal quartiles to assess rates of discordant pairs. Results: Among the 2735 hospital-level quarters based on 714 hospitals included in the study, CDI prevalence (median: 0.46 per 100 patient-admissions) and CDI antibiotic use (median: 8.85 antibiotic-days per 1, 000 days-present) demonstrated only a moderately positive correlation (r = 0.48). Among hospitals in the highest quartile for CDI prevalence, 5.1% were in the lowest quartile for antibiotic use. Among hospitals in the highest quartile for antibiotic use, 5.3% were in the lowest quartile for CDI prevalence, and 54.2% were in the highest quartile for CDI prevalence (G = 0.60; 95% CI: 0.57–0.63). Correlation of hospital-level Clostridioides difficile infection (CDI) prevalence rates and oral vancomycin and fidaxomicin use in U.S. acute care hospitals, 2018 Distribution of hospital-level Clostridioides difficile infection (CDI) prevalence rates and oral vancomycin and fidaxomicin use in ordinal quartiles (Q1–Q4) to access rates of discordant pairs Conclusion: The moderate correlation and discordant rates suggest that vancomycin and fidaxomicin are less frequently used as primary antibiotics in some hospitals; whereas in others, CDI antibiotic use is occurring in the absence of positive laboratory tests for CDI. To further investigate this discordance, there is a need to assess hospitals' prescribing and testing practices in an ongoing manner. These findings may be useful to serve as baseline for measuring progress of appropriateness of treatment and testing for CDIs. Disclosures: All Authors : No reported disclosures